Acquisition of joint capital equipment for the centre for micro and nano science and technology university of rijeka: scanning (scanning) electron microscope (sem) (MENA Report, 2014)
Contract award notice: procurement subject is the acquisition of joint capital equipment for the centre for micro and nano science and technology, university of rijekascanning (scanning) electron microscope (sem), cpv 38511100-1. the system should be offered as a whole, including all the equipment and supplies required for its installation and verification system. procurement...